Identification and characterization of the anti-SARS-CoV-2 activity of cationic amphiphilic steroidal compounds. Issue 1 (31st December 2022) - Borin, Alexandre; Coimbra, Laís D.; Bispo-dos-Santos, Karina; Naciuk, Fabrício F.; Fontoura, Marina; Simeoni, Camila L.; Gomes, Giovanni F.; Amorim, Mariene R.; Gravina, Humberto D.; Shimizu, Jacqueline Farinha; Passos, Amanda S. C.; de Oliveira, Isadora M.; et al.
ABSTRACT: The ongoing COVID-19 pandemic caused a significant loss of human lives and a worldwide decline in quality of life. Treatment of COVID-19 patients is challenging, and specific treatments to reduce COVID-19 aggravation and mortality are still necessary. Here, we describe the discovery of a novel class of epiandrosterone steroidal compounds with cationic amphiphilic properties that present antiviral activity against SARS-CoV-2 in the low micromolar range. Compounds were identified in screening campaigns using a cytopathic effect-based assay in Vero CCL81 cells, followed by hit compound validation and characterization. Compounds LNB167 and LNB169 were selected due to their ability to reduce the levels of infectious viral progeny and viral RNA levels in Vero CCL81, HEK293, and HuH7.5 cell lines. Mechanistic studies in Vero CCL81 cells indicated that LNB167 and LNB169 inhibited the initial phase of viral replication through mechanisms involving modulation of membrane lipids and cholesterol in host cells. Selection of viral variants resistant to steroidal compound treatment revealed single mutations on transmembrane, lipid membrane-interacting Spike and Envelope proteins. Finally, in vivo testing using the hACE2 transgenic mouse model indicated that SARS-CoV-2 infection could not be ameliorated by LNB167 treatment. We conclude that anti-SARS-CoV-2 activities of steroidal compounds LNB167 and LNB169 are likely host-targeted, consistent with the properties of cationic amphiphilic compounds that modulate host cell lipid biology. Although effective in vitro, protective effects were cell-type specific and did not translate to protection in vivo, indicating that subversion of lipid membrane physiology is an important, yet complex mechanism involved in SARS-CoV-2 replication and pathogenesis.